Confirmation of acute nitrate poisoning differentiating from anthrax in three Indian indigenous cattle (Journal of Advanced Veterinary and Animal Research, 2014)
This article reports cases of nitrate poisoning in Indian indigenous cattle breeds comprising two Gir cows aging 4 years each, and one Barugur cow at 1.5 years of age. The cattle with case history of sudden death and oozing of partially clotted blood from the anal opening were brought to the Central University Laboratory (CUL), Center for Animal Health Studies (CAHS), Tamil Nadu Veterinary and Animal Sciences University (TANUVAS) for diagnostic investigation with a suspicion of anthrax. According to anamnesis, all the animals were clinically normal and did not reveal any abnormality on the previous day. The animals were fed with recently harvested sorghum leaves and stalks.  Smears examined for anthrax were found negative. Biological test (mice inoculation) for anthrax was also negative. Gross lesions on necropsy examination of the carcases were suggestive of nitrate intoxication. Finally, nitrate intoxication of these cattle was confirmed by chemical and toxicological analysis of fodder, rumen content, aqueous humor, liver, kidney and urine. http://dx.doi.org/10.5455/javar.2015.b51